Optimizing the Outcome of Pediatric Metastatic Neuroblastoma in a Nontransplant Setting in a Developing Country: Retrospective Study from a Tertiary Cancer Center in India - Nair, Manjusha; R., Prasanth V.; Thankamony, Priyakumari; Rajeswari, Binitha; S., Guruprasad C.; George, Preethi Sara (Indian Journal of Medical and Paediatric Oncology, 2024)
Objective This article estimates the survival of children over 1 year of age diagnosed with metastatic neuroblastoma (NB) and treated in a nontransplant facility and determines the factors affecting survival.Materials and Method Case records of children aged 1 to 14 years treated for metastatic NB in our center from January 2008 to December 2017 were studied. Patients received conventional chemotherapy followed by surgery, radiotherapy, and metronomic maintenance chemotherapy.Results Eighty-nine patients with metastatic NB received treatment. Mean age was 3.5 years and male:female ratio was 1.1:1. The most common primary site was suprarenal (55%) and the most common site of metastasis was bone marrow (76%). Forty percent patients had multiple metastatic sites. Mean baseline lactate dehydrogenase (LDH) was 3724 U/L (range 303–16609 U/L) and 65% patients had LDH > 750 U/L. Fifty-three patients (59.6%) had good response to chemotherapy as evidenced by clearance of metastatic disease, but out of them, 43 patients (81%) progressed subsequently. Twenty-six patients underwent surgery and 12 patients received maintenance therapy. Seventy-four patients (86%) developed recurrence and all but one died. Median time to recurrence and death were 9 months (range 0–120 months) and 10 months (range 1–123 months), respectively. At a median follow-up of 72 months (range 15–135 months), 16 patients are alive, with 5-year disease-free survival and overall survival of 17.6 and 18.4%, respectively. Age, baseline LDH, chemotherapy regimen, and response to treatment significantly affected survival.Conclusion Younger age, lower baseline LDH, and good response to chemotherapy appear to confer survival advantage in pediatric metastatic NB, and may be used for optimization of treatment in the nontransplant setting in developing countries.
Keywords: pediatric; metastatic neuroblastoma; survival; developing country; India